Józefowi Piłsudskiemu... w rocznicę odzyskania niepodległości 11 listopada 1918 r [blok znaczków podziemnych] . To Józef Piłsudski... on the Independence Day 11 November 1918. Sheet of unofficial stamps - Poczta Solidarności Walczącej. (Poczta Solidarności Walczącej, 1984)
Black, grey and blue print on white paper, without perforatio.n Sheet, with "Poczta Solidarności Walczącej" imprint, consists of one stamp which represents Marshal Józef Piłsudski. The sheet is decorated with the image of the badge of the Piłsudski's Legions and two captions: the dedication below, date and place above. Price: 120 zł per stamp.